2023
DOI: 10.1002/ajoc.202200591
|View full text |Cite
|
Sign up to set email alerts
|

Decade Advance of Isatin in Three‐component Reactions

Abstract: Isatin is an important building block in organic synthesis. The electron-deficient carbonyl in C-3 site is similar to aldehyde. C-3 carbonyl is also able to function as the Onucleophile. Devise methodologies about three-component reactions of isatin have been reported in this decade. This review highlights these multicomponent reactions by triggered mechanisms. We hope it will promote future research in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 153 publications
0
11
0
Order By: Relevance
“…Multicomponent reactions (MCRs) are reactions of three or more compounds to form a single product. 1 The most important feature of MCRs is the single-step operation without the need to separate intermediates, which avoids the protection and de-protection of functional groups, saves resources, reduces environmental pollution and greatly improves the synthetic efficiency, meeting the requirements of atom economy, as advocated by green chemistry. 2 With continuous pollution of the environment, the design of efficient and new green MCRs has become one of the main research challenges in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Multicomponent reactions (MCRs) are reactions of three or more compounds to form a single product. 1 The most important feature of MCRs is the single-step operation without the need to separate intermediates, which avoids the protection and de-protection of functional groups, saves resources, reduces environmental pollution and greatly improves the synthetic efficiency, meeting the requirements of atom economy, as advocated by green chemistry. 2 With continuous pollution of the environment, the design of efficient and new green MCRs has become one of the main research challenges in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…As simple substrates, alkenes are considered as one of the most basic building blocks in synthetic chemistry [3] . Multicomponent reactions (MCRs), especially three‐component reactions, will reduce the number of steps and waste generation, with high efficiency in forming complicated molecules from simple starting materials [4] . The direct transformation of alkenes via three‐component reactions into diverse organoselenium or organosulfur compounds are highly attractive [5] …”
Section: Introductionmentioning
confidence: 99%
“…[3] Multicomponent reactions (MCRs), especially three-component reactions, will reduce the number of steps and waste generation, with high efficiency in forming complicated molecules from simple starting materials. [4] The direct transformation of alkenes via three-component reactions into diverse organoselenium or organosulfur compounds are highly attractive. [5] In our opinion, a summary classified by mechanisms and target products will do much help for the further research.…”
Section: Introductionmentioning
confidence: 99%
“…Isatin and its spirocyclic derivatives often possess biological or pharmacological properties, such as anticancer, antituberculosis, antiviral, antimalarial, and antibacterial activities, and play significant roles in the dye industry and the pharmaceutical field. 52,53 Interestingly, we recently found that the spiropolymer could induce the apoptosis of cancer cells and display anticancer activity, while its small-molecular model compound did not have this characteristic. 48 In this contribution, all spiropolymers are obtained in good isolated yields (up to 92.6%) and high molecular weights (up to 56800 g/mol), and their chemical structures are confirmed by NMR and FTIR spectra.…”
Section: Introductionmentioning
confidence: 99%